Quality of life for patients with chronic obstructive pulmonary disease, pulmonary tuberculosis and with a combination of two nosologies - M. V. Moiseeva; I. A. Viktorova; N. V. Bagisheva; A. V. Mordyk; D. I. Mordyk (Лечащий Врач, 2021)
The characteristics of changes in the quality of life (QOL) in patients with chronic obstructive pulmonary disease (COPD), tuberculosis (TB) and COPD + TB were analyzed. It was concluded that aggravation of COPD, comorbid presence of TB, as well as possible complications of COPD leads to lower quality of life of patients and requires a comprehensive approach to the management of these patients.